2015
DOI: 10.5194/gmd-8-1577-2015
|View full text |Cite
|
Sign up to set email alerts
|

A high-resolution ocean and sea-ice modelling system for the Arctic and North Atlantic oceans

Abstract: Abstract. As part of the CONCEPTS (Canadian Operational Network of Coupled Environmental PredicTion Systems) initiative, a high-resolution (1/12 • ) ice-ocean regional model is developed covering the North Atlantic and the Arctic oceans. The long-term objective is to provide Canada with short-term ice-ocean predictions and hazard warnings in ice-infested regions. To evaluate the modelling component (as opposed to the analysis -or data-assimilation -component, which is not covered in this contribution), a serie… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
83
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(85 citation statements)
references
References 73 publications
2
83
0
Order By: Relevance
“…2d). The too strong intensity of the modelled sea ice velocity was already shown with NEMO3.1-LIM2 (Dupont et al, 2015). However, the model captures the seasonality of drift speed with higher values in summer, when concentration and thickness are the lowest, and lower values in winter, when concentration and thickness are high.…”
Section: Model Evaluationmentioning
confidence: 99%
“…2d). The too strong intensity of the modelled sea ice velocity was already shown with NEMO3.1-LIM2 (Dupont et al, 2015). However, the model captures the seasonality of drift speed with higher values in summer, when concentration and thickness are the lowest, and lower values in winter, when concentration and thickness are high.…”
Section: Model Evaluationmentioning
confidence: 99%
“…During the last decade, an extensive effort has been made to simulate eddying ocean, and different models have been implemented in regional, near-global, and fully global domains (e.g. Maltrud and McClean, 2005;Chassignet et al, 2009;Oke et al, 2013;Drakkar Group, 2014;Metzger et al, 2014;Dupont et al, 2015). In this context, we developed a global eddying configuration, where eddying means that the numerical simulation is eddy-resolving in the majority of deep ocean regions, while it is mostly eddy-permitting on the continental shelves or in weakly stratified polar latitudes.…”
Section: Introductionmentioning
confidence: 99%
“…The relaxation timescales were set to 1 day for inflow and 15 days for outflow. These values are identical to those used in Dupont et al (2015), but differ from the original NAA configuration (Hu and Myers, 2013). Our preliminary experiments suggested that these changes were needed to prevent salinity drift.…”
Section: Initial and Lateral Boundary Conditions Runoff And Atmosphmentioning
confidence: 65%